Teatro e formação humana na velhice: o teatro do oprimido no programa AFRID - Tavares, Laila Maria Medeiros (2018)
This master's work was developed in the Graduate Program in Education of the Federal University of Uberlândia, in the Research Line "Work, Society and Education", with the general objective to investigate the impacts of the Theater of the Oppressed, considering it a powerful tool pedagogical, in the third age. For this, we devoted some ​notes to elucidate the methodological trajectory traced in the course of this work, identifying the methodological nature of this dissertation and listing the research instruments used. It was also presented the main theoretical aspects approached by the thought of Karl Marx from his dialectical historical materialist method, seeking to understand the place destined to the old body under the aegis of capitalism. In this context, we sought to clarify the main aspects that cover old age, using as main theoretical reference the work "Old Age", by Simone de Beauvoir, also signaling to the phenomenon of population aging. Some reflections were also made on the approximations between the theories of Augusto Boal and Paulo Freire, considering that the guiding thread of this research - the Theater of the Oppressed - was inspired by the Pedagogy of the Oppressed. In the face of the theoretical principles of Karl Marx, Augusto Boal and Paulo Freire, discussed in this paper, it was proposed to think of capitalist society as a theater, analyzing the role of ideological rigging of the State, specifically the school IEA, in determining social masks . In addition, we attempted to elucidate the locus of this research, in order to contemplate the AFRID program and the AFRIDança group, which constitute the target audience of this dissertation, also weaving some relevant understandings, arising from the analysis of the information and the data obtained with the aid of methodological instruments. ​Finally, we verified the hypothesis initially raised by this research, highlighting the benefits provided by the Theater of the Oppressed in the third age, addressing the need to raise the old age's question and to remove the stereotypes associated with it, making the phenomenon of aging not a social problem, but an achievement.